Peran GBKP Pamulang dalam Mengatasi Krisis Ekologi - Nofyn, Hafizzatul; Nurdin, M. Amin (Inklusiva: Jurnal Studi Agama-Agama, 2024)
This research analyzes the role of the Batak Karo Protestant Church (GBKP) in Pamulang in addressing the ecological crisis. The main focus of this study is how GBKP implements the service theme "Creatively Caring for the Environment" to make a positive contribution to environmental sustainability. The research method used is descriptive qualitative with an ecotheology approach. Data were collected through observation, interviews, and documentation. The results of the study show that GBKP has implemented various activities that support environmental conservation. These activities include the publication of a creative environmental care guidebook, tree planting activities, food waste management, education on plastic use, as well as the socialization and collection of used cooking oil waste. The implementation of this service theme not only helps in maintaining environmental cleanliness and sustainability but also opens up economic opportunities for the surrounding community through waste management. The conclusion of this study emphasizes that places of worship have a significant role in addressing the ecological crisis through various community and faith based activities.